Intraperitoneal IL-6 signaling in incident patients treated with icodextrin and glucose bicarbonate/lactate-based peritoneal dialysis solutions - Opatrna, Sylvie; Lysak, Daniel; Trefil, Ladislav; Parker, Clare; Topley, Nicholas (Peritoneal dialysis international, 2012)
OBJECTIVE: In this study, we compared the activity of interleukin-6 (IL-6), a marker of ongoing peritoneal inflammation and biocompatibility, and its other signaling components, the soluble IL-6 receptor (sIL-6R) and soluble Gp130 (sGp130), in peritoneal effluent from patients treated with icodextrin-based (E) peritoneal dialysis (PD) solution and glucose-based bicarbonate/lactate-buffered (P) solution. METHODS: Using baseline peritoneal ultrafiltration capacity, 33 stable incident PD patients were allocated either to P only (n = 20) or to P plus E for the overnight dwell (n = 13). We used ELISA to determine IL-6, sIL-6R, and sGp130 in timed overnight effluent at 1, 6, and 12 months after PD initiation. Flow cytometry was used to measure expression of IL-6R and Gp130 on isolated peritoneal leukocytes at the same time points. Peritonitis was an exclusion criterion. RESULTS: At all time points, levels of IL-6 and sIL-6R, and the appearance rates of IL-6 (90.5 pg/min vs. 481.1 pg/min, p < 0.001; 138.6 pg/min vs. 1187.5 pg/min, p < 0.001; and 56.1 pg/min vs. 1386.0 pg/min, p < 0.001), sIL-6R (2035.3 pg/min vs. 4907.0 pg/min, p < 0.01; 1375.0 pg/min vs. 6348.4 pg/min, p < 0.01; and 1881.3 pg/min vs. 5437.8 pg/min, p < 0.01), and sGp130 (37.6 ng/min vs. 65.4 ng/min, p < 0.01; 39.2 ng/min vs. 80.6 ng/min, p < 0.01; 27.8 ng/min vs. 71.0 ng/min, p < 0.01) were significantly higher in peritoneal effluent from E-treated patients than from P-treated patients. Expression of IL6-R and Gp130 on individual leukocyte types isolated from PD effluent did not differ between E- and P-treated patients. The numbers of white blood cells present in effluent were higher in E-treated than in P-treated patients at all time points, but no significant differences were seen in the differential counts or in the number of exfoliated mesothelial cells. The IL-6 parameters in effluent from E-treated patients correlated with their plasma C-reactive protein. Despite the increased activation of the IL-6 system, no increase in peritoneal permeability as assessed by the dialysate-to-plasma ratio of creatinine in E effluent or by systemic inflammation was observed throughout the study. CONCLUSIONS: Higher levels of IL-6, its soluble receptors, and leukocyte expression were observed in E-treated than in P-treated patients, but this difference was not associated with alterations in peritoneal permeability or systemic inflammation during 1 year of follow-up. Leukocyte counts in effluent from E-treated patients were within the normal range previously reported for glucose solutions. This lack of clinical consequences may be a result of a parallel rise in sIL-6R and sGp130, which are known to control the biologic activity of IL-6. The utility of IL-6 level determinations, in isolation, for assessing the biocompatibility of PD solutions is questionable.
Keywords: Peritoneal Dialysis, Continuous Ambulatory; hydrogenuhličitany; signální transdukce; Signal Transduction; Icodextrin; Humans; lidé středního věku; fixní kombinace léků; kontinuální ambulantní peritoneální dialýza; Lactic Acid; Female; Aged; mladý dospělý; dospělí; Interleukin-6; ELISA; senioři; lidé; glukosa; Enzyme-Linked Immunosorbent Assay; Bicarbonates; dialyzační roztoky; časové faktory; Glucans; Adult; Dialysis Solutions; peritoneum; Follow-Up Studies; ženské pohlaví; icodextrin; Male; Flow Cytometry; Middle Aged; interleukin-6; Glucose; Young Adult; průtoková cytometrie; Peritoneum; glukany; Drug Combinations; mužské pohlaví; prospektivní studie; kyselina mléčná; Time Factors; následné studie; Prospective Studies